Evaluación de la calidad del agua para consumo humano en la ciudad universitaria de la universidad nacional de trujillo, 2019 - Rodríguez Villanueva, Rocio Pilar (2019)
This research was carried out with the objective of determining the quality of water for human consumption in Ciudad Universitaria - Universidad Nacional de Trujillo during the year 2019. The quality parameters established in the Water Quality Regulation for Human Consumption were analyzed, in water samples taken from six central points: 5 coffee shops and a tubular well, on 6 different occasions, taking as a guide the “Protocol of procedures for sampling, preservation, conservation, transport, storage and reception of water for human consumption”. The physico-chemical and microbiological parameters were analyzed, based on "Standard methods for the examination of water and wastewater". Subsequently, the respective statistical calculations were made to then compare the results with the Maximum Permissible Limits (LMP) established by Ministerio de Salud. It was determined that the water that supplies Ciudad Universitaria - Universidad Nacional de Trujillo does not keep the required environmental quality standards; Therefore, it is not suitable for human consumption. This implies and justifies the need to implement improvements in the water supply system in Ciudad Universitaria that allows improving the quality of water for human consumption and reducing health risks in the college community